„You Won’t Break the Ice and Won’t Talk about It“: Mental Health Professionals’ Difficulties in Providing Assistance to Individuals who Later Suicide - Rimkevičienė, Jurgita; Grigienė, Dovilė; Geležėlytė, Odeta; Mažulytė-Rašytinė, Eglė (Psichologija, 2023)
Accessible and effective mental health services for people at risk of suicide are one of the cornerstones of suicide prevention. However, some people suicide while receiving such help, and it is important to understand the reasons for this. In the absence of a direct way to reveal the experiences of people who have received services and subsequently suicided, the professionals providing mental health services are an important source of information on this process. The main aim of this study was to describe the main difficulties experienced by professionals supporting people who later suicided. The sample included 15 mental health professionals (7 psychiatrists, 6 medical psychologists, and 2 social workers) who experienced patient suicide. The data were collected using semi-structured interviews, which were then analysed using thematic analysis. The following themes were identified in the stories of the participants: lack of collaboration from the patient, specific topics that were challenging to work with, treatment limitations, difficulties in assessing suicide risk, reactions experienced when working with the suicidal patient, and the role of the patient’s relatives. Therefore, the results of this study speak about the challenge of being with a patient in a suicidal crisis, who is not inclined to accept help, while bearing the limitations of the system and oneself as a specialist. This causes intense experiences of helplessness and anger.